The Case for a Portuguese Web Search Engine - Silva, Mário J. (2009)
This paper presents the case for a search engine for the Portuguese Community. Preservation of publications of historical interest for future access, obtaining knowledge about the preferences and interests of our society in the information age and intelligence gathering for security and protection are examples of national interests addressed by such system. This paper also introduces the architecture and design of tumba!, a new Internet search engine for the Portuguese Web. Tumba! proposes a new repository architecture and uses innovative ranking and presentation algorithms. It is designed to take profit of our unique knowledge of this web making it a platform that could work as testbed for research and evaluation of new ideas in Web information retrieval and the computational processing of Portuguese